Response of Gamma-Ray Spectrum During Ockhi Cyclone - Datar, Gauri; Vichare, Geeta; Raghav, Anil; Bhaskar, Ankush; Sinha, A. K.; Nair, K. U. (Frontiers in Earth Science, 2020)
Cyclone Ockhi hit Sri Lanka and southern parts of India in Nov-Dec 2017 with a devastating social impact. The present paper reports that the cyclone had a significant effect on the γ-ray flux measured by NaI (Tl) detector. An overall decrease is observed in the γ-ray flux during the passage of cyclone; however, a detailed investigation revealed that different energies show varying results. In the energy range between 250 keV – 450 keV, a decrease up to ~ 14% is observed, whereas an increase up to ~ 45% is observed in the energy range between 600 keV – 2.7 MeV. The energies above 2.7 MeV do not show any change. This is the first-ever observation of the varying effects of the cyclone with the energy bands of the γ-ray spectrum. We found that the increase observed in the energy range of 600 keV – 2.7 MeV is primarily associated with the increase in the terrestrial radioactivity (peaks of Rn-222 daughters), which is due to the rainfall brought over by the cyclone. The high energy γ-rays originating from cosmic ray are not affected due to the cyclone. The study indicates that the decrease in the lower energy range of the γ-ray flux could be due to the attenuation caused by the increased tropospheric air-mass associated with the cyclone over the observation site.